2015
DOI: 10.1590/0047-2085000000094
|View full text |Cite
|
Sign up to set email alerts
|

Alterações de comportamento na encefalite herpética: um caso polimórfico e de difícil manejo

Abstract: RESUMOA encefalite herpética é uma doença de alta mortalidade que deve ser diagnosticada e tratada rapidamente. Cefaleia, febre e alteração de comportamento compõem a tríade clássica. Há escassos estudos sobre o tema e nenhum a respeito do manejo das manifestações psiquiátricas. O relato de caso se refere a paciente de 35 anos, que manifestou a tríade clássica, sendo diagnosticado e tratado corretamente. Após um mês, apresentou desorganização do comportamento e agitação, sendo reinternado. Foi descartada recid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Another interesting finding of that work was the correlation between violence and organic brain disorders. Other studies report difficulty in managing these patients, 38,39 and the topic deserves further investigation . In our work, the diagnoses of personality disorder were factored into the analysis whenever they were present in the reports.…”
Section: 36mentioning
confidence: 89%
“…Another interesting finding of that work was the correlation between violence and organic brain disorders. Other studies report difficulty in managing these patients, 38,39 and the topic deserves further investigation . In our work, the diagnoses of personality disorder were factored into the analysis whenever they were present in the reports.…”
Section: 36mentioning
confidence: 89%
“…The narrative review 9 found on the topic focuses on studies of patients diagnosed with COVID‐19 and concludes that there are several descriptions of reports of psychosis and COVID‐19 infection in the world, in general, with satisfactory responses to antipsychotics, but so far it is not possible to relate the virus directly to psychosis. It is noteworthy that cases of organic origin, such as viral infections, reveal several behavioral changes, with psychotic and delusional symptoms being relatively frequent 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that cases of organic origin, such as viral infections, reveal several behavioral changes, with psychotic and delusional symptoms being relatively frequent. 10,11 A controlled study 12 in England divided 361 people into groups exposed or not exposed to isolation and COVID-19, seeking to correlate the development of paranoid symptoms with several factors. It was found that employed individuals and students had a higher incidence of paranoia.…”
Section: Discussionmentioning
confidence: 99%
“…Eles também encontraram aumento de risco de violência em populações com transtornos mentais de origem orgânica. Outros estudos também descreveram dificuldades no manejo clínico da agressividade/impulsividade na literatura em pacientes com esses transtornos (Monteiro et al, 2015;Oliveira et al (2), 322-341, jun. 2016 2015).…”
Section: Discussionunclassified